Clinical outcomes and risk factors of post-polypectomy microperforation in patients with colorectal neoplasia: a case-control study - Seung Yong Shin; Min Soo Cho; Jinhoon Nam; Jie-Hyun Kim; Young Hoon Yoon; Hyojin Park; Jeonghyun Kang; Jae Jun Park (Therapeutic Advances in Gastrointestinal Endoscopy)
Background: Colonoscopic polypectomy significantly reduces the incidence of colorectal cancer, but it carries potential risks, with colonic perforation being the most common and associated with significant morbidity. Objectives: This study evaluated the clinical outcomes and risk factors of microperforation during colonoscopic polypectomy. Design: A retrospective cohort study. Methods: We retrospectively reviewed the patients’ records who underwent colonoscopic polypectomy and subsequent plain radiographic examination to monitor perforation. Patients with pneumoperitoneum detected on plain radiography were enrolled. Patients who underwent adverse event-free colonoscopic polypectomies within 1 week of each case and were matched 2:1 by age and sex to the cases were selected as controls. Results: Microperforations occurred in 12 patients (8 males; age: median 64.5 years). Polyps with microperforations were more frequent in the right colon (83.3% vs 33.3%). Endoscopic mucosal resection with precutting (EMR-P; 16.7% vs 0.0%) or hot-snare polypectomy (8.3% vs 0.0%) was more frequently performed in the microperforation group. Muscle fibers at the polypectomy site were more frequently visible in the microperforation group (58.3% vs 8.3%). By multivariate analysis, right colon location and visible muscle fibers were independent risk factors for microperforation. All patients with microperforation received intravenous antibiotics and were advised to fast. Patients responded well to these conservative treatments and were discharged after a median of 3 (2–6.75) days of hospital stay. Conclusion: Our data suggest that conservative treatment is feasible and could be the primary management option for selected patients with microperforations postcolonoscopic polypectomy. Right-sided colonic polyps and visible muscle fibers predispose to microperforations.